Association between malocclusion severity and psychosocial issues among adolescents - Yasmin Pissolati Mattos Bretz; Gabriela Luíza Nunes Sousa; Júnia Maria Cheib Serra-Negra; Saul Martins Paiva; Lucas Guimarães Abreu (Universidad de Concepción., 2019)
Aim: To evaluate the association between malocclusion severity and psychosocial issues among Brazilian adolescents. Methods: The study sample consisted of 120 adolescents between 11 and 12 years, patients at the Dental School of the Federal University of Minas Gerais. Psychosocial issues were assessed by means of two questions, through which the adolescents were asked about whether a classmate had teased or called them names due to the condition of their teeth, or whether the adolescents had felt upset due to their teeth. The higher the response scores the greater the psychosocial impact. Malocclusion was evaluated with the Dental Aest-hetic. Index, with assignment of individuals to the following sub-groups: mild malocclusion (DAI≤25), moderate malocclusion (DAI=26-30), definite malocclusion (DAI=31-35) and severe malocclusion (DAI≥36). Results: Adolescents' mean age was 11.50 years. The more severe the malocclusion the greater the frequency of episodes of teasing or name-calling because of the condition of the teeth (p=0.010), and the greater the frequency of episodes when the adolescents had felt upset due to their teeth (p=0.001). Individuals with severe malocclusion had a higher frequency of episodes during which they were teased or called names due to the condition of their teeth when compared to individuals with mild malocclusion (p=0.013). Individuals with severe malocclusion had a higher frequency of episodes in which they felt upset due to their teeth when compared to individuals with mild malocclusion (p<0.001), individuals with moderate malocclusion (p=0.002), and those with defined malocclusion (p=0.001). Conclusion: Severe malocclusion was associated with psychosocial issues among adolescents.